Genital neoplasm-imitating gastrointestinal stromal tumor. Case report and literature review - Bieńkiewicz, Andrzej; Dec, Grażyna; Suzin, Jacek; Szwalski, Jarosław; Wójcik-Krowiranda, Katarzyna; Gottwald, Leszek; Wierzbowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2003)
Malignant gastrointestinal stromal tumor is a rare neoplasm of upredictable clinical course and still unknown etiology and pathogenesis. It makes up 1–3% of malignant tumors of this location. Large tumor size, necrosis, low histological differentiation, and high mitotic activity are found as poor prognostic factors. Although it can imitate genital tumors GIST is rarely the subject of gynecologist’s concern. We describe the case of a 74-years-old woman with GIST treated surgicaly because of genital tumor suspition. Surgical procedures and supportive treatment acquaintance can complement gynecological surgery knowledge.